Wellness and Motivation in a Physical Education Course Over a Semester: Examining the Interaction Effects that Motivation has on Wellness Outcomes - John Lothes II; Rachel Kantor (The Ohio State University Libraries, 2021)
Objective: This study reports the results that physical education classes have on college students' overall wellbeing and motivation over the course of a semester. This study examines the pre/post outcomes of a physical education course on 12 dimensions of wellness and motivation from the start of the semester to the end of the semester. Participants: College students (N = 1193) taking Physical Education 101 (PED101) over the course of a semester. Methods: Beginning (pre) and end (post) of the semester assessments for wellbeing and motivation were conducted using the Wellness Inventory. Quantitative outcomes from the Wellness Inventory were compared pre/post as well as demographic variables (e.g., gender & exercise frequency). Regression analysis was also conducted to examine how motivation may affect wellness.  Results: All 12 dimensions of wellness and motivation showed increases from the start of the semester to the end of the semester. Motivation was also positively correlated with increases in wellness scores. The results found statistically significant changes between the pre- and post-assessments for all dimensions of wellness outcomes and motivation scores. There were also significant changes between the pre- and post-assessments when investigating differences based on sex. Conclusion: PED101 courses can be useful interventions to help move college students towards wellness.